Systemic scleroderma: An approach from plastic surgery (2018)
Introduction: Systemic sclerosis (SSc) is an autoimmune disease of the connective tissue that is clinically characterized by dermal thickening, which occurs due to the accumulation of connective tissue, and may involve other organs and the limbs. The multifactorial etiology of this disease is related to alterations in remodeling interactions of the extracellular matrix (ECM), immune function and presence of proliferative vasculopathy under genetic and environmental influence.Objective: To conduct a literature review on medical and surgical management from the point of view skin, hand and finger lesions surgery, as well as facial alterations in patients with systemic scleroderma.Materials and methods: A bibliographic search was performed in the Medline, LILACS, PubMed, EMBASE and Current Contents databases, using the keywords “systemic scleroderma”, “plastic surgery”, “hand” and “ulcers”.Results: SSc requires a multidisciplinary management, since pharmacological therapy is indicated for some cases and complementary surgical management is better for others.Conclusion: This pathology significantly affects the skin by causing lesions ranging from digital ulcers to facial atrophy, which are susceptible to management by plastic surgery.